A model for oxidation-driven surface segregation and transport on Pt-alloys studied by atom probe tomography - Bagot, P; Kreuzer, H; Cerezo, A; Smith, G (2011)
Using a purpose-built 3D atom probe, we have previously shown that exposure to oxidising gases (NO, N2O, O2) induces Rh surface segregation in Pt-Rh alloys, the extent of which is strongly dependent on treatment temperature, crystallographic plane and the presence of ternary alloy additions. In this paper, the segregation trends identified on three different crystallographic surfaces of Pt-Rh are analysed using thermodynamic and kinetic arguments. The segregation model we present is generic for diffusion on alloy surfaces in the presence of active gases. From it we obtain activation energies and diffusion coefficients for the processes of metal-oxide species diffusion both perpendicular to and laterally across the surface. Using these we propose a simple model for the interaction of chemically active gases with the surfaces of such alloys. Applying this understanding to sequential oxidation/reduction treatments would in principle allow improved control of the surface composition of alloy catalysts. Related applications of this model include optimisation of core-shell catalyst nanoparticles. © 2011 Elsevier B.V. All rights reserved.